Screening of thermostable and organic solvent tolerant lipase producing fungi in solid state bioconversion of palm kernel cake - Riyadi, Fatimah Azizah; Alam, Md. Zahangir; Salleh, Md Noor; Mohd Salleh, Hamzah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Special consideration has been focused on the utilization of lipase enzyme as a suitable alternative method for biodiesel production, which is expected to be more stable and practical. However, the high production costs as well as low productivity have hindered the marketable production of biodiesel using the commercial lipase. Isolation of lipases from filamentous fungi, particularly found in agricultural wastes has attracted special interest due to their potential towards developing more sustainable and economical applications. Only lipase possessing thermal stability and organic solvent tolerant can distinctively enhance the biodiesel production. Therefore, in the present study, isolation of thermostable- organic solvent tolerant fungal strains from palm kernel cake (PKC) were conducted based on their ability to grow at 45oC on YpSs (yeast extract + starch + agar) media and in the presence of organic solvent. The isolates were screened based on the clearing zone methods on phenol red as well as on tween 80 agar media. Four isolates were screened for potential lipase production. These isolates were incubated under Solid State Fermentation (SSF) at 45oC for 7 days with PKC as substrate. The most promising strain with the potential to produce lipase was PKC12B2, which showed satisfactory enzyme activity.